The influence of RS738409 I148M polymorphism of patatin-like phospholipase domain containing 3 gene on the susceptibility of non-alcoholic fatty liver disease. Issue 19 (14th May 2021) - Akkiz, Hikmet; Taskin, Emre; Karaogullarindan, Umit; Delik, Anil; Kuran, Sedef; Kutlu, Ozlem
Abstract : Abstract: We aimed to elucidate the frequency of polymorphic genotypes and alleles of patatin-like phospholipase domain containing 3 rs738409 polymorphism and its possible associations with non-alcoholic fatty liver disease (NAFLD) and non-alcoholic steatohepatitis in a cohort from Turkey. We enrolled 200 patients diagnosed with NAFLD and genotyped for rs738409 I148M polymorphism by real-time polymerase chain reaction, particularly by melting curve analysis. SPSS analysis software was used for statistical significance. Continuous variable values were expressed as mean ± standard deviation. Significant statistical level was chosen as p   =  0.05. Our results demonstrate in a cohort from Turkey that rs738409 C > G polymorphism (I148M) of patatin-like phospholipase domain containing 3 gene is significantly able to affect individuals to have NAFLD in unadjusted regression model. Consistent with the previous studies in other populations, our study group showed a significantly higher risk of having NAFLD in unadjusted regression model but not in the adjusted model indicating that non-genetic factors such as age and sex may be responsible for the association. However, independent studies need to validate our findings with a larger group of NAFLD patients, as well as in different ethnic cohorts.